2014
DOI: 10.3390/cancers6031500
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Cancer and Oxidative Lipoxygenase Activity are Intimately Linked

Abstract: Cancer and inflammation are intimately linked due to specific oxidative processes in the tumor microenvironment. Lipoxygenases are a versatile class of oxidative enzymes involved in arachidonic acid metabolism. An increasing number of arachidonic acid metabolites is being discovered and apart from their classically recognized pro-inflammatory effects, anti-inflammatory effects are also being described in recent years. Interestingly, these lipid mediators are involved in activation of pro-inflammatory signal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 109 publications
1
103
0
6
Order By: Relevance
“…For example, interleukin‐6 can induce CRP and specific acute‐phase response protein, activate STAT3 and NF‐κB, prevent apoptosis and promote tumor cell proliferation . By secreting factors to form inflammatory microenvironments, inflammatory cells can robustly promote tumors …”
Section: Discussionmentioning
confidence: 99%
“…For example, interleukin‐6 can induce CRP and specific acute‐phase response protein, activate STAT3 and NF‐κB, prevent apoptosis and promote tumor cell proliferation . By secreting factors to form inflammatory microenvironments, inflammatory cells can robustly promote tumors …”
Section: Discussionmentioning
confidence: 99%
“…Previous computational study has showed that ginger components could be optimized as lead for the treatment of neurodegenerative diseases, such as Alzheimer's disease, because of its wide spectrum of potential targets which include acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), β-site amyloid precursor protein cleaving enzyme (BACE-1), human carboxylesterase (hCE-1), and nitric oxide synthase (NOS) among others [24].The lipoxygenases has been reported to have intimately linked activities [21]. The report of Nievergelt et al [17] indicated that 10-shogaol, 1-dehydro-6-gingerdione, and particularly the whole lipophilic ginger extract partially activated the 5-HT1Areceptor (20-60% of maximal activation).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the cyclooxygenase enzyme and LOX in the inflammatory process were extensively explored [37][38][39]. It was shown that the metabolism of arachidonic acid generated a host of proinflammatory metabolites.…”
Section: Lipoxygenase (Lox) Inhibitory Assessmentmentioning
confidence: 99%